2020
DOI: 10.1111/eth.13005
|View full text |Cite
|
Sign up to set email alerts
|

A behavioural trait displayed in an artificial novel environment correlates with dispersal in a wild bird

Abstract: Behaviour shown in a novel environment has important consequences for fitness in many animals. It is widely studied with standard tests by placing the individuals into an unfamiliar experimental area, that is the so‐called open‐field or novel environment test. The biological relevance of traits measured under such artificial conditions is questionable and could be validated by establishing a link with variables that truly reflect exploration in the wild. Our aim in this field study was to characterize behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
(124 reference statements)
0
5
0
1
Order By: Relevance
“…We thank Alfredo Sánchez-Tójar and Raphaël Royauté for feedback in the methodological approach, all authors of (Schuett et al 2015) Acyrthosiphon pisum lab (Lapiedra et al 2018) Anolis sagrei wild (Piquet et al 2018) Atlantoxerus getulus wild (Foster et al 2017) Chlorostoma funebralis lab (Keiser et al 2018) Chlorostoma funebralis lab (Jablonszky et al 2018) Ficedula albicollis wild (Niemelä et al 2019) Gryllus bimaculatus lab (Santostefano et al 2017) Gryllus bimaculatus lab (Fisher et al 2015) Gryllus campestris wild 10 (Niemelä et al 2015) Gryllus campestris wild (Akçay et al 2015) Melospiza melodia amaka wild (Marshall et al 2016) Mungos mungo wild (Réale & Festa-Bianchet 2003) Ovis canadensis canadensis wild (van Overveld et al 2015)…”
Section: Aknowledgementsmentioning
confidence: 99%
“…We thank Alfredo Sánchez-Tójar and Raphaël Royauté for feedback in the methodological approach, all authors of (Schuett et al 2015) Acyrthosiphon pisum lab (Lapiedra et al 2018) Anolis sagrei wild (Piquet et al 2018) Atlantoxerus getulus wild (Foster et al 2017) Chlorostoma funebralis lab (Keiser et al 2018) Chlorostoma funebralis lab (Jablonszky et al 2018) Ficedula albicollis wild (Niemelä et al 2019) Gryllus bimaculatus lab (Santostefano et al 2017) Gryllus bimaculatus lab (Fisher et al 2015) Gryllus campestris wild 10 (Niemelä et al 2015) Gryllus campestris wild (Akçay et al 2015) Melospiza melodia amaka wild (Marshall et al 2016) Mungos mungo wild (Réale & Festa-Bianchet 2003) Ovis canadensis canadensis wild (van Overveld et al 2015)…”
Section: Aknowledgementsmentioning
confidence: 99%
“…Modelos mixtos que muestran la relación entre la latencia para alimentarse y el tiempo que tardaron los gorriones macho que salieron de la caja en alimentarse en presencia de un objeto extraño (NO). Jablonszky et al, 2020), supporting the hypothesis that personality may play a significant role in the success of bird invasions. MacGregor-Fors et al (2019) recently showed that house sparrows are bolder -in terms of alert distanceswhere it is exotic, invasive, and abundant, suggesting a density-dependent process in urban areas.…”
Section: Discussionunclassified
“…We first captured male and female birds that were subsequently used to elicit songs from the focal males and to reflect the listener’s perspective (these birds are systemically referred as stimulus birds hereafter), but on plots at least 500 m away from the plots where we made song recordings. Hence, based on the short dispersal distance of this species ( Könczey et al 1992 ; Jablonszky, Krenhardt, et al 2020 ) and the infrequent movement between study plots ( Garamszegi, Török, et al 2004 ), we can reasonably assume that it was unlikely that the tested males encountered the stimuli previously. However, we cannot entirely exclude this potential confounding effect, but we can argue that the effect of familiarity should cause only some random noise, as we used stimulus birds with more than one focal males.…”
Section: Methodsmentioning
confidence: 96%